Pengaruh Kualitas Produk, Harga Dan Digital Marketing Terhadap Keputusan Pembelian Sepatu Aerostreet (Studi Pada Mahasiswa Universitas Islam Malang) - Mahfudi Mahfudi; Muhammad Agus Salim; Afi Rachmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to determine and analyze the effect of product quality, price and digital marketing on the decision to purchase Aerostreet shoes for students at the Islamic University of Malang. The type of research used in this research is quantitative research. The independent variables used are product quality, price, digital marketing, while the dependent variable is purchasing decisions. The sample used in this study were 105 respondents who purchased Aerostreet shoes. Data collection techniques using a questionnaire. The analytical method used is validity test, reliability test, classical assumption test, multiple linear regression analysis, hypothesis testing, with the help of SPSS software. The results of the study show that the variables of product quality, price, digital marketing partially and simultaneously have a positive and significant effect on purchasing decisions. Keywords: Purchase Decision, Product Quality, Price, Digital Marketing